2004
DOI: 10.1161/01.atv.0000116692.85043.ef
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Lipids in a National Birth Cohort Study

Abstract: Objective-To investigate the association between birth weight and lipid levels in a 53-year-old birth cohort from England, Scotland, and Wales. Methods and Results-Lipid levels were obtained from nonfasting blood samples, collected at the most recent follow-up of the MRC National Survey of Health and Development, for 2559 men and women. Regression models indicated that in men, a 1-kg increase in birth weight was associated with a 0.13-mmol/L decrease (95% CI: Ϫ0.23, Ϫ0.01) in total cholesterol at age 53 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 62 publications
5
24
0
Order By: Relevance
“…Such sex differences have been reported before [7][8][9][10] and have been attributed to small numbers of female participants 7 (not a limiting factor in the BT cohort) and the premenopausal status of participating women. 9 Premenopausal women have lower TC concentrations than men of a similar age.…”
Section: Birth Weight and Adult Tcmentioning
confidence: 55%
See 2 more Smart Citations
“…Such sex differences have been reported before [7][8][9][10] and have been attributed to small numbers of female participants 7 (not a limiting factor in the BT cohort) and the premenopausal status of participating women. 9 Premenopausal women have lower TC concentrations than men of a similar age.…”
Section: Birth Weight and Adult Tcmentioning
confidence: 55%
“…6 -10 Four of these studies reported regression coefficients: Ϫ0.19, Ϫ0.16, Ϫ0.25, and Ϫ0.15 mmol/L change in TC per 1-kg increase in birth weight (all adjusted for current weight or BMI). 6,7,9,10 The corresponding coefficient in BT men was Ϫ0.09 mmol/L per 1 kg. It is possible that the smaller effect size observed in BT men arose from the use of self-reported birth weight (the 4 comparison studies used medical records).…”
Section: Birth Weight and Adult Tcmentioning
confidence: 94%
See 1 more Smart Citation
“…4,6 The association between total cholesterol and birth weight is reported to be stronger for men than women; and the positive relationship between birth weight and high-density lipoprotein (HDL) is most apparent in postmenopausal women. 7,8 Where associations have been shown between birth weight and lipids, it remains unclear whether these might be a direct effect of undernutrition or caused by confounding as a result of parental factors. The association may also be mediated by a shared genetic mechanism.…”
mentioning
confidence: 99%
“…2 A further large study published since this review, in contrast, found an association in females but not males and when these results were incorporated into the meta analysis the original sex difference was 'abolished'. 3 Despite over 30 publications reporting regression coefficients separately for men and women there have been only five large (>1000 individuals) [2][3][4][5][6] such studies in adults. In addition, some studies have used recalled birth weight or had limited data on potential confounding factors that could impact total cholesterol levels in adult life.…”
Section: Introductionmentioning
confidence: 99%